PHYSICO-CHEMICAL INDEX OF A PASTE-LIKE DETERGENT - Kadirova N. B; Abdurahimov A.A; Salixanova D.S. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article shows the possibilities of obtaining paste-like detergents based on secondary resources and waste of fat-and-oil production. The basic physico-chemical properties of the obtained detergents have been studied. It has been established that the use of wastewater formed during the hydration process containing phospholipids, triacylglycerides and polysilicon acids with surface-active and emulsifying properties will positively affect the washing and cleaning abilities.